Public debts, fiscal balance and sustainability: What can African governments learn from debt sustainability models? - Gladys Awinpoak Abindaw Nabieu; Michael Minlah; David Mensah (Cogent Economics & Finance, 2023)
This paper examines the impact of public debt on fiscal balance. This study uses the standard debt equation in a fiscal reaction and impulse response functions framework to assess the trajectory of public debt and its sustainability within the Sub-Sahara region from 1980-2017. From the estimations of the fiscal reaction function, the lagged primary balance significantly affects the fiscal deficits of Sub-Saharan African countries. Also, public debts to the gross domestic product beyond a threshold of fifty percent are positive and significantly associated with the primary balance. Fiscal deficits contribute to increases in the debt stock of about 120% over the ten-year for the Sub-Sahara region. The results imply that fiscal governance is required to constrict fiscal deficits whenever debt stock levels approach a certain threshold and growth. Therefore, stakeholders should implement enhanced fiscal policy rules on fiscal balance, public debts, and economic growth to improve debt sustainability.
Keywords: 330; debt sustainability; economic growth; fiscal policy; primary balance; Public debt